An Overview of Electrical Characterization Techniques for Biological Cell - Mat Sulaiman, Abdul Hafiz; Ahmad, Ida Laila; Abdul Rahim, Ruzairi; Pusppanathan, Jaysuman; Hanafi, Dirman; Mohamad, Elmy Johana; Abd Shaib, Mohd Fadzli; Leow, Pei Ling; Abdul Wahab, Yasmin; Ridzuan Aw, Suzanna (International Journal of Integrated Engineering, 2019)
In this paper, various electrical characterization techniques available for biological cell have been systematically reviewed. It covers both invasive and non-invasive approaches for population and single cell based studies. Examples of invasive technique consist of probing and patch clamp that measures the ionic current. However, depending on the applications, the non-invasive techniques are far more superior and popular. Some of the technique such as dielectric spectroscopy, electrorotation and dielectrophoresis measures the cell conductivity and dielectric constant. Furthermore, previous researchers proved that non-invasive technique may reduce the harmful effect on the cell due to electrical exposure. The review compares in terms of working principles, sample applications, advantages and limitations of each technique.